Knowledge representation, reasoning, and declarative problem solving - Baral, Chitta (Cambridge University Press, 2003)
Baral shows how to write programs that behave intelligently, by giving them the ability to express knowledge and to reason. This unique book will appeal to practising and would-be knowledge engineers wishing to learn more about the subject in courses or through self-teaching.